2016
DOI: 10.1136/annrheumdis-2016-eular.1715
|View full text |Cite
|
Sign up to set email alerts
|

FRI0224 Comparison of Efficacy and Safety of Rituximab Biosimilar, BCD-020, and Innovator Rituximab in Patients with Active Rheumatoid Arthritis Refractory To TNFA Inhibitors

Abstract: BackgroundBCD-020 is the first Russian rituximab (RTX) biosimilar which was approved for medical use in lymphoma patients in Russia and some CIS countries. Previous preclinical and clinical studies showed that BCD-020 is highly similar to innovator RTX. Since there are several differences in mechanism of action of RTX in NHL and RA it is recommended to conduct separate clinical studies in oncology and autoimmune indications to prove similar efficacy and safety of biosimilar and original medicine.ObjectivesThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…IFX CT-P13 also demonstrated clinical efficacy in another RCT of MTX-IR RA 46. Efficacy was also formally proven in placebo-controlled RCTs with the ADA bsDMARDs ABP50147 and SB5,48 with the ETN bsDMARDs HD20349 and SB4,50 with the IFX bsDMARD SB251 and with the RTX bsDMARD BCD-020 52…”
Section: Resultsmentioning
confidence: 89%
“…IFX CT-P13 also demonstrated clinical efficacy in another RCT of MTX-IR RA 46. Efficacy was also formally proven in placebo-controlled RCTs with the ADA bsDMARDs ABP50147 and SB5,48 with the ETN bsDMARDs HD20349 and SB4,50 with the IFX bsDMARD SB251 and with the RTX bsDMARD BCD-020 52…”
Section: Resultsmentioning
confidence: 89%
“…bsDMARDs have been shown to be safe and effective when used as an alternative to boDMARDs (moderate evidence). There were no differences in ACR20 and ACR70 response rates, disease activity (moderate evidence), or severe adverse events of the bsDMARDs adalimumab, etanercept, infliximab, and rituximab compared with their respective boDMARDs [134][135][136][137][138][139][140]. The development of anti-drug antibodies was similar between bsDMARDs and boDMARDs (moderate evidence), and lower for the bsDMARD of etanercept compared with the boDMARD (high evidence) [134].…”
Section: Biosimilar Drugsmentioning
confidence: 94%
“…Limited published preclinical data are available; similarities between BCD-020 and reference rituximab in terms of quality characteristics, in vitro biological activity, toxicology, and PK/PD profiles in nonhuman primates have been demonstrated [113]. Phase III clinical testing was conducted in patients with FL or marginal zone lymphoma, and in rheumatoid arthritis [113,114]. Both studies showed comparable efficacy, PK/PD, and safety profiles for reference rituximab and BCD-020.…”
Section: Biomimicsmentioning
confidence: 99%